2009
DOI: 10.1021/ma802848t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small Molecule and Polymeric Urethanes, Thiourethanes, and Dithiourethanes: Hydrogen Bonding and Thermal, Physical, and Mechanical Properties

Abstract: The hydrogen bonding behavior of a homologous series of small molecule and polymeric urethanes, thiourethanes, and dithiourethanes was investigated in solution, melt, and solid states. The relative hydrogen bonding strengths in both small molecule and polymer systems were evaluated, and the results were compared to theoretical calculations of hydrogen bonding strength. The results for NMR and FTIR analysis of the small molecule models indicated that the NH protons on the carbamate and thiocarbamates have great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 43 publications
0
70
0
Order By: Relevance
“…The use of thio-urethanes in the polymer coatings and molded parts industry has been widely reported [33,36]. Those networks have demonstrated the capacity of improving mechanical properties, more specifically toughness, due to a more homogeneous polymer network formation in comparison to simple urethane counterparts [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of thio-urethanes in the polymer coatings and molded parts industry has been widely reported [33,36]. Those networks have demonstrated the capacity of improving mechanical properties, more specifically toughness, due to a more homogeneous polymer network formation in comparison to simple urethane counterparts [36].…”
Section: Discussionmentioning
confidence: 99%
“…Those networks have demonstrated the capacity of improving mechanical properties, more specifically toughness, due to a more homogeneous polymer network formation in comparison to simple urethane counterparts [36]. Recently, work by our group has demonstrated that this technology can be translated into dental materials applications through the relatively simple approach of including pre-polymerized thio-urethane oligomers into the methacrylate matrix [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen bonding distribution and micro/nano-phase segregation behavior of polyurethanes as function of their precursors chemistry, physical properties or synthesis procedure are important factors when predicting chemical and physical characteristics of potential new materials (3,(9)(10)(11). While typically, talking or writing about STPUEs morphology, it has been referred to as "polyurethanes microstructure," it should be pointed that the incompatibility between hard segments (HS) and soft segments (SS) lead to a nanoescale phase separation with hard nano-domain ranging between 5-20 nm size (3,(12)(13)(14)(15), which truly trend to assemble into 3D spherulite-like microstructures (14).…”
Section: Introductionmentioning
confidence: 99%
“…Poly(thiourethane)s, poly(thioester)s and poly(thiocarbonate)s have been synthesized and investigated mainly as potential plastics with high thermal and chemical resistance, as well as with high refractive index for optical applications (i.e., lenses and optical fibers) [1,[4][5][6][7].…”
mentioning
confidence: 99%